Yo-Yo intermittent recovery test level 2: Cardiorespiratory response and performance in professional soccer players, comparison between under 20 and over 20 years old players - Cabrera Hernández, M. A.; Tafur Tascon, L. J.; García-Corzo, S. A.; Arias Londoño, H.; Quiñonez Sánchez, A.; Carreño Cano, G.; Hurtado Gutiérrez, H.; Tejada Rojas, C. X. (Journal of Human Sport & Exercise, 2018)
Purpose: The aim of this study was to compare the older players (O20) and the younger ones (U20) of the Colombian Professional National League 2015 champion team in cardiopulmonary responses and performance, using the Yo-Yo Intermittent Recovery Test level 2 (YYIR2). Methods: Nine O20 and nineteen U20 were voluntarily evaluated. All subjects were monitored for heart rate, and a continuous breath-to-breath recording was carried out while they performed the YYIR2. The Student T test and the Pearson correlation were used for the statistical analysis. Results: A significant difference in distance covered and speed in the ventilatory threshold between U20 players (280 ± 85,3 m) (16,6 ± 0,3 km/h) and O20 players (373 ± 113,1 m) (17 ± 0,3 km/h) was observed. Only in the U20 group, a significant correlation between the variables oxygen uptake in the ventilatory threshold (V.O2atVT) and performance in the test (Dmax), V.O2 at VT and maximum speed (Smax), peak oxygen uptake (V.O2peak) and Smax and V.O2peak and Dmax was observed. Conclusion: The only variables that differentiated the performance in the population was the analysis of the distance and the speed at the time of the ventilatory threshold.Intermittierender Yo-Yo-Wiederherstellungstest Stufe 2: Kardiorespiratorische Reaktion und Leistung bei professionellen Fußballspielern, Vergleich zwischen Spielern unter und über 20 Jahren.